Digital Literacy Hoax Information in Indonesian Tourism Area - K. Y.S. Putri; Vera Wijayanti Sutjipto; Wiratri Anindhita; Nada Arina Romli; Yesi Andriani; Diva Rheva Deianeira (Journal of Digital Marketing and Communication, 2022)
The COVID-19 pandemic has drastically reduced tourism in Indonesia. Information, both legal and unclear, is milling about in cyberspace. Researchers are concerned with this problem by asking research questions about how much influence digital literacy has on attitudes toward responding to hoax news in new media. The purpose of the study was to determine the effect of digital literacy on attitudes toward responding to hoax news in new media. The concepts used are digital literacy, new media, and audience attitudes in responding to information in new media. Previous research has assisted this research in supporting this research. Questionnaires were distributed to the respondents in this study, accompanied by several interviews with several sources. The results of the validity and reliability tests of this study were good enough that they could proceed to the next statistical stage. The results of the descriptive research are positive. The condition of the COVID-19 pandemic has made tourism in Indonesia worse for tourist areas. Hoax information has made the area worse both economically and on the other hand. The relationship between digital literacy and the respondents' attitudes in this study is strong. The null hypothesis in this study was rejected, so the alternative research hypothesis was accepted. The novelty in this study is that the relationship between the two variables is in a pandemic condition that has lasted for two years in Indonesia. The impact of this pandemic has made tourist areas in Indonesia very problematic for the economy and people's lives. Suggestions for research include: additional research can describe or add additional analysis in solving societal problems.